Isolation and Identification of Microorganism in Brown Sorghum Tempeh (Sorghum bicolor) and Its Potency for Degrading Starch and Protein. - Andayani, Pratidina; Wardani, Agustin Krisna; Murtini, Erni Sofia (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Brown sorghum (Sorghum bicolor) is rarely used for food product due to lower digestibility level of starch and protein compared to other cereal. Fermentation is one of the method for increasing the cereal digestibility. The fermentation can be optimized when the condition are under controlled. To achieve such kind of condition, the contribution of a certain microorganism should be identified. Thus, the aim of this research was to isolate and to identify the microorganism during sorghum fermentation. Furthermore, the potency of isolates for degrading the starch and protein was also investigated.Â The isolation and identification of microorganism in sorghum tempeh resulted 25 isolates of lactic acid bacteria from genus Lactococcus sp, Enterococcus sp or Streptococcus sp, 10 isolates of yeast from genus Saccharomyces sp, and 1 isolate of mold from genus Rhizopus sp. Three isolates showed the potency for degrading starch i.e. two isolates of lactic acid bacteria and one isolate of mold. The potency for degrading protein was shown by mold isolate. It was found that the amylolytic activity of two bacteria isolates were 0.401 U/ml and 0.343 U/ml, whereas mold isolate was 2.406 U/ml. Mold isolate showed proteolytic activity of 1.007 U/ml.Keywords: sorghum, isolation, identification, microorganism, starch, protein